If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 7q = 5q Solving -6 + 7q = 5q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-5q' to each side of the equation. -6 + 7q + -5q = 5q + -5q Combine like terms: 7q + -5q = 2q -6 + 2q = 5q + -5q Combine like terms: 5q + -5q = 0 -6 + 2q = 0 Add '6' to each side of the equation. -6 + 6 + 2q = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 2q = 0 + 6 2q = 0 + 6 Combine like terms: 0 + 6 = 6 2q = 6 Divide each side by '2'. q = 3 Simplifying q = 3
| x+3=2x+1-x+2 | | 8. 4m+5n=25 | | 3(2x+4)=-2(4x-13) | | 4x^3-3x=13 | | -8y-9=-10y+9 | | -3/2=-2/5y-5/3 | | 1-2x+3=2x+8 | | -3/2=2/5y-5/3 | | ax-b=c(x-a) | | 6+14u=8 | | 13+3(3x+8)=x+3 | | -(x+3)+2=2x | | -8y-9=-10+9 | | 2/3u-8/9=-7/5 | | 6x=ln(10/9) | | 4x+-2y=18 | | 4k(-3mk)= | | 2/5×25 | | 5+7x(3+2)-16= | | 3x+4+x=4-x | | 36b+-10=-6 | | 45=5x-9+x | | -(1/7×3/2)= | | Y/10=9/4 | | 4c-16=8 | | -12u+7=-1 | | 3x^2-7x+3=2x^2-4x+3 | | j-3=7+6j | | 16/1 | | y^2-2xy+3=0 | | 7p-10=6p | | 5/50=t/4 |